Atividade antiulcerogênica de cissampelos sympodialis eichl. (menispermaceae) em modelos animais - Sales , Igor Rafael Praxedes de (2016)
Cissampelos sympodialis Eichl. (Menispermaceae) is an endemic species in Brazil, popularly known as "Milona", "Jarrinha" or "Orelha-de-onça". This species was selected for this study considering the chemotaxonomic (alkaloids and flavonoids) and ethnopharmacological criteria, due to this species be popularly used to treat inflammatory disorders. This study aimed to evaluate the acute preclinical toxicity and anti-ulcer activity of the ethanolic extract (EtOHE-Cs) and alkaloids total fraction (TAF-Cs) obtained from aerial parts of C. sympodialis. In acute toxicity, doses of 300 and 2000 mg/kg EtOHE-Cs were administered orally (p.o.). Our experiment conditions shows that, this type of doses did not induce signs of toxicity in female mice and 50% of lethal dose (LD50) is equal to or greater 5000 mg/kg according to the OECD 423 guide. For TAF-Cs was founded that the animals treated with the dose of 2000 mg/kg showed straub tail and analgesia. In addition, the LD50 of this substance being approximately 1000 mg/kg. To evaluate the gastroprotective activity using induced acute models of gastric ulcers were used: ethanol and containment of gastric juice in rats, anti-inflammatory non-steroidal drug (NSAID - piroxicam) and stress (immobilization and cold) in mice. In ulcer model induced by ethanol the results showed that carbenoxolone (100 mg/kg), EtOHE-Cs or TAF-Cs (62.5; 125; 250 and 500 mg/kg – v.o.) reduced the ulcerative lesion area (ULA) of 97, 69, 75, 94, 98; 97, 88, 90, 94, 95% (p<0,001) respectively in comparison with the negative control. In the same model, treatment with carbenoxolone (100 mg/kg), EtOHE-Cs (500 mg/kg) or TAF-Cs (250 mg/kg) improved histological parameters analyzed. Considering ulcers induced by NSAIDs, cimetidine (100 mg/kg), the EtOHE-Cs or TAF-Cs (62.5; 125; 250 and 500 mg/kg – p.o.) reduced the ulcerative lesion index (ULI) in 43, 59, 60, 64, 76; 47, 51, 62, 75 and 78% (p<0,001), respectively. In the lesions induced by stress cimetidine, EtOHE-Cs or TAF-Cs at the same doses reduced ULI at 44, 37, 38, 42, 52; 57, 39, 54, 75 and 76% (p<0,001), respectively. Ulcers induced by restraining of the gastric juice (pylorus ligation) treated with cimetidine (100 mg/kg), EtOHE-Cs (500 mg/kg) and TAF-Cs (250 mg/kg) decreased the ULI at 35, 42 and 40 % (p.o.) (p<0,001) and 39, 34 and 33% (intraduodenally – i.d.) (p<0,01), respectively. To investigate the mechanisms of samples of C. sympodialis involved in gastroprotective activity it was evaluated the antisecretory or neutralizing mechanisms of the gastric acid secretion and cytoprotective, antioxidant and immunoregulatory properties. Treatments (p.o. and i.d.) with EtOHE-Cs (500 mg/kg) and TAF-Cs (250 mg/kg) did not alter biochemical parameters of gastric juice, suggesting that gastroprotective activity does not involve antisecretory or neutralizing mechanisms. The gastroprotective activity of EtOHE-Cs (500 mg/kg) involves participation of sulfhydryl groups, nitric oxide, KATP, mucus and prostaglandins. The gastroprotection promoted by the TAF-Cs (250 mg/kg) involves the participation of sulfhydryl groups, mucus and prostaglandins. EtOHE-Cs (500 mg/kg) (p<0,001) and TAF-Cs (250 mg/kg) (p<0,01) showing antioxidant activity by an increase in reduced glutathione (GSH) levels compared to the negative control in ethanol-induced gastric ulcers. The EtOHE-Cs (500 mg/kg) reduces the levels of pro-inflammatory cytokines, interleukin 1 beta (IL-1β) (p<0,001) and tumor necrosis factor (TNF-α) (p<0,05) and levels of anti-inflammatory interleukin were increased, interleukin 10 (IL-10) (p<0,001) compared to the negative control. Treatment with TAF-Cs (250 mg/kg) did not alter IL-1β and TNF-α levels, however this treatment increased IL-10 levels compared to the negative control (p<0,001). In the cysteamine-induced duodenal ulcer lansoprazole (30 mg/kg), EtOHE-Cs (500 mg/kg) or TAF-Cs (250 mg/kg) reduced the ULA in 93, 49; 61 and 89% (p<0,001), respectively. Considering these results, it was possible to suggest that C. sympodialis and derivates presents antiulcerogenic activity and the gastroprotective activity of this species involves cytoprotective, antioxidants and immunoregulatory mechanisms.